Hannah Arendt: política e responsabilidade no julgamento de Eichmann - Tizzo, Fabiano Miranda do Nascimento (2015)
This paper aims to analyze Hannah Arendt s (1906-1975) positions on the trial of Otto Adolf Eichmann (1906-1962). This analysis will use the book Eichmann in Jerusalem, produced by the author after having personally witnessed the defendant's trial, a Nazi bureaucrat appointed as responsible for the transport system and bureaucracy that led people to deportation and to death in the Hitlerist period in Germany (1933-1945) under his government orders. After Germany's defeat in World War II, Eichmann escapes and lives in Argentina with a new identity. In 1960, the Israeli secret service captures him and takes him to trial in the District Court of Jerusalem. He was charged with fifteen crimes, including crimes against humanity, crimes against Jewish people and for being a membership of a criminal organization. Throughout his trial, he was analyzed by Hannah Arendt the renowned philosopher whom exposes a number of reflections on the case and on the subject Eichmann. In addition, Arendt discusses the legality of Eichmann s capture and the moral issues that arise throughout the trial, as well as his personal and legal responsibility in the crimes of which he was accused